Celebrating the source water festivities of Southeast Asia - Poh, Lindy (Association of Southeast Asian Nations Committee on Culture and Information (ASEAN-COCI), 2009)
"This book features the iconic and beloved water celebrations of the ASEAN countries as well as introduces the lesser known rituals and festivities that have shaped the cultural and social life of the region."--Publisher's website.